PENGARUH KONSERVATISME AKUNTANSI DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP NILAI EKUITAS PERUSAHAAN SEKTOR PERTAMBANGAN MINYAK DAN GAS BUMI YANG TERDAFTAR DI BURSA EFEK INDONESIA - B51111094, Hendra Gunawan (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This study aims to determine how the application of accounting conservatism and mechanisms of good corporate governance in the company's annual report presentation. In addition, to analyze the relationship between accounting conservatism and good corporate governance mechanism against the equity value of a company engaged in the mining sector of oil and gas that are listed in the Indonesia Stock Exchange. The company's equity value is measured using sleep price value (PBV). Conservatism accrual accounting assessed based on the activity of the company's operations, namely by subtracting the net income to cash flows from operating activities of the company. Good corporate governance mechanisms used in this study was measured by its independence, the board of directors, independent directors, audit committees and audit quality. The sample used in this study is as much as 7 (seven) companies mining oil and gas that are listed in the Indonesia Stock Exchange with the observation period 2011-2013. Sampling using purposive sampling technique that uses secondary data and analyzed with multiple linear regression analysis method. Hypothesis testing using partial test (t test) and a simultaneous test (F test). The results showed that the variable accounting conservatism and audit committees have a significant influence on the company's equity value. While variable commissioners, independent commissioner and audit quality does not significantly influence the company's equity value. Keywords : accounting conservatism, the mechanism of good corporate governance, equity value of the company